2022
DOI: 10.3390/healthcare10081429
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Should Be Focused on When Analyzing Physical Activity in Hospitalized Older Adults after Trunk and Lower Extremity Fractures—A Pilot Study

Abstract: Although the importance of resting in bed for hospitalized older adults is known, current methods of interpreting physical activity (PA) recommend the use of a broad definition of sedentary behavior (SB) that includes 0–1.5 metabolic equivalents (METs) of sleep (SL) and sitting. We investigated the characteristics of PA by conducting a cross-sectional study of 25 older adults with trunk and lower extremity fractures. The intensity of their PA was interpreted as SL (0–0.9 METs), SB (1–1.5 METs), low-intensity P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The participants engaged in sedentary behavior (SB) for approximately 22 h per day, with about 13 h of SB during the daytime. Light-intensity physical activity (LIPA) accounted for approximately 2 h, while moderate-to-vigorous physical activity (MVPA) was around 0.5 h. A previous study conducted in Japan reported SB time of 9 h, LIPA of 2.5 h, and MVPA of 0 h [ 37 ]. In comparison, the participants in our study (with FIM motor item scores of 68) exhibited lower levels of independence in ADL compared to those in the previous study (with FIM motor item scores of 82).…”
Section: Discussionmentioning
confidence: 99%
“…The participants engaged in sedentary behavior (SB) for approximately 22 h per day, with about 13 h of SB during the daytime. Light-intensity physical activity (LIPA) accounted for approximately 2 h, while moderate-to-vigorous physical activity (MVPA) was around 0.5 h. A previous study conducted in Japan reported SB time of 9 h, LIPA of 2.5 h, and MVPA of 0 h [ 37 ]. In comparison, the participants in our study (with FIM motor item scores of 68) exhibited lower levels of independence in ADL compared to those in the previous study (with FIM motor item scores of 82).…”
Section: Discussionmentioning
confidence: 99%